Luteoloside prevents lipopolysaccharide‐induced osteolysis and suppresses RANKL‐induced osteoclastogenesis through attenuating RANKL signaling cascades. Issue 2 (23rd August 2017) - Song, Fangming; Wei, Chengming; Zhou, Lin; Qin, An; Yang, Mingli; Tickner, Jennifer; Huang, Yuanjiao; Zhao, Jinmin; Xu, Jiake
Abstract : Bone destruction or osteolysis marked by excessive osteoclastic bone resorption is a very common medical condition. Identification of agents that can effectively suppress excessive osteoclast formation and function is crucial for prevention and treatment of osteolytic conditions such as periprosthetic joint infection and periprosthetic loosening. Luteoloside, a flavonoid, is a natural bioactive compound with anti‐inflammation and anti‐tumor properties. However, the effect of Luteoloside on inflammation‐induced osteolysis is unknown. Here, we found that Luteoloside exhibited a strong inhibitory effect on lipopolysaccharide (LPS)‐induced osteolysis in vivo. In addition, Luteoloside suppressed RANKL‐induced osteoclast differentiation and abrogated bone resorption in a dose‐dependent manner. Further, we found that the anti‐osteoclastic and anti‐resorptive actions of Luteoloside are mediated via blocking NFATc1 activity and the attenuation of RANKL‐mediated Ca 2+ signaling as well as NF‐κB and MAPK pathways. Taken together, this study shows that Luteoloside may be a potential therapeutic agent for osteolytic bone diseases associated with abnormal osteoclast formation and function in inflammatory conditions. Abstract : Luteoloside may be a potential therapeutic agent for osteolytic bone diseases associated with abnormal osteoclast formation and function in inflammatory conditions.